2018
DOI: 10.1007/s00264-018-3952-5
|View full text |Cite
|
Sign up to set email alerts
|

Delay of total hip arthroplasty to advanced stage worsens post-operative hip motion in patients with femoral head osteonecrosis

Abstract: The progression of ONFH negatively affected post-operative hip ROM as well as baseline hip ROM at the time of THA. Surgeons should consider a delay of THA negatively affects the hip ROM after the arthroplasty, when they determine the treatment modality for ONFH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Another aspect to consider is that patients may have had some operations before the THA or may have wait a long time before arthroplasty which may in some circumstances worsen the functional result [36].…”
Section: Total Hip Arthroplasty and Osteonecrosismentioning
confidence: 99%
“…Another aspect to consider is that patients may have had some operations before the THA or may have wait a long time before arthroplasty which may in some circumstances worsen the functional result [36].…”
Section: Total Hip Arthroplasty and Osteonecrosismentioning
confidence: 99%
“…Our study showed that if the threshold probability was between 0.06 and 0.96, as shown by the constructed decision curves, the AI-based nomogram could predict postoperative ONFH compared with treating either all or no patients. This indicated that early postoperative prediction using this hybrid of patient and radiograph variables can be useful for the application of early interventions that may even allow for a reasonable delay of the onset of arthroplasty (50). Substantial positive rehabilitation can be applied after accurate predictions are obtained after the operation for patients with a lower prediction probability, which will also relieve patient anxiety (51).…”
Section: Discussionmentioning
confidence: 99%
“…However, substantial high-level evidence implicates that if THA is performed too early in young, active patients, it shows poor long-term outcomes, shorten implant survival time, and requires at least one and even multiple revisions [ 7 ]. Clinically, for those who are young or have not yet experienced secondary osteoarthritis, the surgeons tend to choose hip preservation treatment and delay the time of THA until the final stage of ONFH [ 8 ]. Unfortunately, this may increase the risk of postoperative adverse events of THA and compromise its clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, few existing studies have explored the differences in outcomes of THA performed at different ARCO stages, and sporadically published ones are also limited by inadequate design, insufficient study variables and small sample size. For example, Jo et al showed that delaying THA to advanced stage reduced postoperative hip motion in a controlled study of ONFH patients after THA at different ARCO stages [ 8 ]. However, they focused only on hip function and ignored other outcomes such as intraoperative information and postoperative adverse events.…”
Section: Introductionmentioning
confidence: 99%